Determining the Cytotoxic Activity of Cantigi Leaf Extract (Vaccinium varingiaefolium Blume Miq.) on HeLa Cervical Cancer and A549 Lung Cancer Cells - Kosasih, Kosasih; Nurfitriyati, Hasna; Hafidz, Reza (Pharmaceutical Research: Recent Advances and Trends Vol. 5, 2024)
Background: Cervical and lung cancer cases increased worldwide as well as in Indonesia from 2018 to 2020. Cancer treatment often involves multidisciplinary approaches and is uncomfortable. Therefore, alternative medicine from natural ingredients is needed. Previous studies showed that the Cantigi leaf ethyl acetate extract has potent cytotoxic activity on L1210 leukaemia cells (IC50 of 8.29 ppm), on MCF-7 cells (IC50 of 75.23 ppm) and T47D cells (IC50 of 88.89 ppm), but no reports exist on HeLa and A549 cells. The side effects of cancer therapies cause painful and uncomfortable conditions; therefore, complementary and alternative medicine (CAM), including herbal medicine, have become common medical products and practices. Objective: The present study aimed to determine the cytotoxic activity of the ethyl acetate extract of Cantigi leaf on HeLa cells and A549 cells. Methods: Powdered dry young Cantigi leaves were macerated with hexane, followed by ethyl acetate. After vacuum evaporation, the dry extract was characterised and tested for its cytotoxic activity on HeLa cells and A549 cells using the MTT method. Results: The ethyl acetate extract colour was dark green with a distinctive Cantigi odour; it had a water content of 4.3% and an acidic pH of 2.87. It showed functional groups of O-H, C-H (aliphatic), C-H (hydrocarbon), C=N, C=O, and C=C. Finally, the IC50 of the ethyl acetate extract on A549 cells was 74.74±5.29 ppm, while on the HeLa cells, it was 79.69±2.54 ppm. The IC50 value of the ethyl acetate extract of Cantigi leaves for each cancer cell can be determined by changing the graph of the extract concentration versus the percentage of viability of cancer cells into a log of the extract concentration versus the percentage of inhibition of cancer cells. Conclusion: The ethyl acetate extract of Cantigi leaves showed potent in vitro cytotoxic activity on HeLa cervical cancer cells and A549 lung cancer cells.